Reframing Digital Literacy in ELT: Integrating SAMR, AI-TPACK, and Connectivism in the Global South - Nualprasert, Benjapon; Punkhoom , Wunwisa; Jehma, Hambalee (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study investigates digital literacy integration within English Language Teaching (ELT) curricula across Thai local government universities through documentary analysis of 108 courses. Employing frameworks including Technological Pedagogical Content Knowledge (TPACK), Substitution, Augmentation, Modification, Redefinition (SAMR), European Digital Competence Framework (DIGCOMP), and Connectivism, we identify a hierarchical readiness gap: near-universal adoption of foundational skills (DIGCOMP: 93% strong alignment) and technological- pedagogical integration (TPACK: 84%) contrasts sharply with lagging transformative (SAMR: 64%) and networked practices (Connectivism: 50%). Crucially, socio-cultural barriers, teacher-centered traditions, rigid assessment systems, and Western-centric assumptions of learner autonomy explain persistent Connectivism underperformance, particularly in humanities disciplines. Regional disparities (e.g., 20% vs. 68% connectivism alignment across provinces) further reflect infrastructural inequities and pedagogical conservatism. Mirroring Global South trajectories, Thailand’s foundations-first approach prioritizes technical literacy over pedagogical reimagination, leaving graduates ill-equipped for AI-disrupted classrooms. This study proposes three imperatives, including an expanded AI-TPACK model integrating ethical AI governance, hybrid frameworks (e.g., SAMR + HeDiCom) for low-resource contexts, and decolonized digital integration centering cultural responsiveness. These innovations offer replicable pathways for teacher education in resource-constrained ecosystems globally.